Desain Interior Perpustakaan Fakultas Bahasa Dan Seni Universitas Negeri Padang Dengan Konsep Minimalis - Beni Chandra; Heldi Heldi (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The low interest in reading has hampered intellectual abilities in society, especially students, so that libraries are required to be able to keep up with the pace of development of the times with services and infrastructure that meet the needs of space users, but the FBS UNP library has not been optimal in terms of interior design standards. Student complaints such as unstable air circulation, lack of reading space, and incomplete facilities have caused inconvenience, so an interior design of the FBS UNP Library was held with a minimalist concept. The purpose of interior design is to design a library layout that is representative and in accordance with interior design standards in order to create a sense of security and comfort for visitors while in the room. The interior design of the FBS UNP Library refers to the application of library interior design standards in the form of space, variety, hierarchy, lighting, personal areas, and comfort. The design method uses the 4D design method, namely Define (Defining) Design (Design), Develop (Development) and Dissaminate (Dissemination). Data collection is done by way of interviews, observation and documentation. Works are presented in the form of an Artwork Report with the main works being Presentation Mockups, Animation Videos and Presentation Posters.